Participação da cooperativa de trabalho de materiais recicláveis como modalidade da economia solidária na gestão ambiental de resíduos sólidos domiciliares: A experiência de Serra Azul (SP), brasil - Vieira, Elias Antônio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The concept of Solidarity Economy - ES used in this study refers to an area of economicexperiences, rural or urban, nonprofit, to generate employment and income with the potential toorganize and consolidate a model of production and consumption based on self-managementconference aimed at social inclusion. The aim of this paper is to describe data from theoretical andpractical reality of ES, and the application of its principles in setting up ventures for employmentgeneration and income, active environmental management of solid household waste and tailingshighlighting the experience of Serra Azul (SP), Brazil.